Pengaruh Perkembangan Seni Kaligrafi Arab Terhadap Budaya di Indonesia - Salma Azizah; Hikmah Maulani (Jurnal Shaf, 2024)
This research discusses the influence of the development of Arabic calligraphy art on culture in Indonesia. The art of Arabic calligraphy, with its beauty and philosophical meaning, has become an integral part of Islamic culture. In Indonesia, Arabic calligraphy is not only considered a form of visual art, but also as an expression of spiritual values ​​and Islamic aesthetic beauty. This research identifies and analyzes the impact of the development of Arabic calligraphy on various aspects of culture in Indonesia. First, Arabic calligraphy art has made a significant contribution to the development of Indonesian fine arts. His influence is visible in the decorative arts, architecture, and other works of art. Arabic calligraphy is not only an aesthetic element, but also a means of conveying religious and spiritual messages. Second, the art of Arabic calligraphy plays an important role in enriching language culture in Indonesia. Many Arabic words used in calligraphy became part of the local vocabulary, creating linguistic synergy between Arab and Indonesian cultures. Third, the art of Arabic calligraphy also has an impact on religious culture in Indonesia. The use of calligraphy in religious contexts, such as in mosques and other places of worship, creates a deeply spiritual environment and adds value to religious practices. Thus, this research details how Arabic calligraphy not only functions as a visual art medium, but also as an agent of cultural and spiritual change in Indonesia. It is hoped that this in-depth understanding of the impact of Arabic calligraphy art can enrich perspectives on cultural dynamics and diversity in Indonesia.